Handbook of Child Psychology and Developmental Science 2015
DOI: 10.1002/9781118963418.childpsy406
|View full text |Cite
|
Sign up to set email alerts
|

Early Childcare and Education

Abstract: 2 Other federal agencies also oversee, or provide support for, ECCE programs. For example, the Department of the Interior oversees the Indian Child and Family Education program, which includes ECCE services. The Department of Labor has programs that provide supportive services to its clients, including child care services, to enable them to participate in training programs. The Department of Housing and Urban Development's Community Development Block Grant Program for Entitlement Communities can be used for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 286 publications
2
76
1
1
Order By: Relevance
“…Child care quality can be considered the most important aspect in capturing the proximal processes occurring within children’s child care microsystems (Burchinal, et al, 2015). In this study, we measured quality from 6–36 months as provider-child positive interactions and at pre-K as global classroom quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Child care quality can be considered the most important aspect in capturing the proximal processes occurring within children’s child care microsystems (Burchinal, et al, 2015). In this study, we measured quality from 6–36 months as provider-child positive interactions and at pre-K as global classroom quality.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal child care providers are those who view themselves as integral to children’s academic learning, respond to individual children’s needs, and engage children by drawing on their interests to promote ideal learning environments (Burchinal, Magnuson, Powell, & Hong, 2015). Such care providers use their relationships with and knowledge of children to draw them into learning social and academic skills and reinforce that learning in a progressive scaffolded way over time (Bodrova & Leong, 2006; Vygotsky, 2001).…”
Section: Multiple Child Care Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning in the child's first year, >50% of all children experience nonparental child care, and by the preschool years, >75% of children are in some type of nonparental child care (Federal Interagency Forum on Child and Family Statistics, 2011). SES is a strong predictor of child care usage (Burchinal et al, 2015). Not surprising, families are most likely to use child care when parents are employed; increases in maternal employment over the past 40 years largely account for the high proportion 3 of children in child care (Burchinal et al, 2015).…”
Section: Family Demographic Characteristicsmentioning
confidence: 99%
“…Extensive ECEC literature documents positive effects of attending high-quality preschools (3-5 years old) on child development outcomes, such as academic, social or executive function skills (e.g., Abreu-Lima et al 2013;Anders et al 2013;Bryant et al 2003;Burchinal et al 2015;Lehrl, Kluczniok, and Rossbach 2016;NICHD 6 classrooms some previous studies found that the quality of relationships between caregivers and children tended to be higher when group size was lower (e.g., Deynoot-Schaub and Riksen-Walraven 2005;NICHD ECCRN 2000) and when ratios were also lower (e.g., Barros and Aguiar 2010;Cost, Quality, & Child Outcomes Study Team 1995;Jamison et al 2014). Furthermore, significant associations were found between a greater number of adults and higher caregiver sensitivity (e.g., Goelman et al 2006).…”
Section: Importance Of Global Ecec Quality and Caregiver-child Interamentioning
confidence: 99%